Evidence of an early form of the Ashkenazic liturgical rite from the Cairo Genizah - Rand, Michael (The journal of Jewish studies, 2015)
The article looks at the some Genizah evidence that contain piyyutim for various festivals and special Sabbaths belonged to several closely related codicological entities that represent an early form of the Ashkenazic liturgical rite. Topic discussed include the Cairo Genizah, collection of Jewish manuscript; codicological reconstruction of different Jewish booklets; and paleography and the vocalization system of the booklets.